Emotional intelligence vs. general intelligence: Aspects to consider in teaching - José L. Martínez-Rubio; Esther Moraleda; Blanca Rodríguez; Lourdes García-Salmones; Manuel Primo (Laureate Education Inc, 2014)
The main objective of this study was to analyze the way in which emotional competencies (EI) in students are linked to general intelligence (IQ), and how the crossing of the two measurements determines their academic performance. To conduct this research, two tests were applied. First, the TEIQue (Trait Emotional Intelligence Questionnaire) assessment was administered and, secondly, the R scale of the PMA Test (Primary Mental Abilities). The sample consisted of 58 university students between 18 and 51 years old, of which 76% are women and 24% are men. The results show that there is no direct relationship between emotional intelligence and general intelligence. However, it is important to consider the size of the sample, since it presents limitations when interpreting the results. Nonetheless, an interesting finding is the interaction discovered between a performance indicator, such as the selectivity score, and the overall EI score. These results are in line with those found by Schutte et al. (1998). This result is even more significant, if possible, when realizing the selectivity score showed a negative correlation (inverse relationship) with the score on the PMA- R (Reasoning) test. -------------------- Inteligencia emocional vs. inteligencia general: Aspectos a considerar en la docencia Resumen La presente investigación tiene como principal objetivo analizar el modo en el que las competencias emocionales (IE) de los estudiantes se vinculan con su inteligencia general (IQ) y cómo del cruce de ambas medidas determinan su rendimiento académico. Para el desarrollo de esta investigación, se suministraron dos cuestionarios a estudiantes de la Universidad Europea de Madrid. Concretamente, los estudiantes cumplimentaron el cuestionario TEIQue (Trait Emotional Intelligence Questionnaire) para la medición de la Inteligencia emocional y la escala R del Test PMA (Primary Mental Abilities) para la valoración del factor de razonamiento. La muestra está compuesta por 58 alumnos universitarios con edades comprendidas entre 18 y 51 años, de los cuales el 76% son mujeres y el 24% son hombres. Los resultados de esta investigación, aunque no han permitido establecer una vinculación clara entre Inteligencia Emocional e Inteligencia General, han permitido vislumbrar algunas tendencias que relacionan las sub-escalas del cuestionario TEIQue con el factor razonamiento de los estudiantes. A través de esta relación, se han podido establecer perfiles y, a partir de ellos, se han identificado las metodologías docentes más adecuadas para mejorar los resultados académicos de los estudiantes. DOI: 10.18870/hlrc.v4i1.199 PDF document contains both the original in Spanish and an English translation.